Comfortable Menopouse with Ex ercise - irfannuddin (Conferences of Medical Sciences Dies Natalis, 2020)
Menopouse is a health problem related to aging that is sure to be experienced by every woman when she reaches middle age. Menopouse is caused by the decreases of estrogen in ovaries due to the failure of negative feedback mechanism in hormonal reproductive system. The decline of estrogen synthesis will affect on various disorder of multi system organs. An appropriate and regular physical exercise is a form of natural intervention that can be done to improve menopause symptoms and decrease risk of degenerative diseases. It is recommended that resistance training is supervised by a professional, or following proper guidelines to prevent the adverse effects.